Les trans comme parias. Le traitement médiatique de la sexualité des personnes trans en France - Karine Espineira; Maud-Yeuse Thomas (Genre, Sexualité et Société)
Combining their respective experiences and trajectories, the authors of this article use their practical knowledge of the field of trans-identities in order to analyze trans people’s sexuality as it is presented on TV. This allows them to conceptualize the trans figure as a pariah. Sexualities and sexual practices appear to be a cornerstone of the trans question. Can we identify specific stigmatized sexual practices and habits shared by gender outlaws? This article sets out to study the ways that the media treat transgender people’s sexuality (or a-sexuality). At times ordinary and at times exotic figures, at times hyper-sexualized and at times de-sexualized, trans people are presented in the mass media in a manner that tends to foster gender roles and the heteronormative regime.